Ketahanan Tanaman Bunga Matahari (Helianthus annuus L.) terhadap Cekaman Air dengan Aplikasi Hidrogel dan Waktu Penyiraman pada Regosol: Resistance of Sunflower (Helianthus annuus L.) on Water Stress by Application of Hydrogel and Watering Time in Regosol - Lilik Tri Indriyati; Wahyu Purwakusuma; Septi Ichwani (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2021)
Application of hydrogel as soil conditioner can increase water and/or nutrient of coursed textured soil, with a possible reduction of irrigation frequency, and in turn increase plant growth. This research was aimed to investigate application of type of hydrogel and time of watering interval on the growth of sunflower plant, soil water availability, and plant resistance to water stress, and to verify the effect of combination of hydrogel type and watering time interval on sunflower growth on Regosol from Dramaga, Bogor. The experiment was arranged in completely randomized factorial design with two factors, that were hydrogel type which was consisted of no hydrogel application as control (H0), hydrogel of Terracottemâ (H1), and hydrogel of synthetic super absorbent (H2); and watering time interval which was consisted of once in 5 days of watering (P1), once in 10 days of watering (P2), and once in 15 days of watering (P3). Hydrogels application was conducted shortly before two weeks old seeds of IPB BM1 genotype sunflower were transplanted in pot containing Regosol which was equivalent to 10 kg of oven- dry weight. Variables observed were soil moisture (soil water content), soil water retention in some soil-water matric suction (pF), leaf area, stem diameter, and root length. Results of experiment showed that hydrogel application significantly increased the water availability for plants in dried soil condition as a result of long time interval of watering, stem diameter of plant, and root length of sunflower compared with no hydrogel application (control). Soil moisture, stem diameter, and root length of treatment with hydrogel of H1 were not significantly different with that of H2. Time interval of watering significantly affected leaf area, stem diameter, and soil moisture. The leaf area, stem diameter of plant, and soil moisture in once watering in 15 days (P3) were significantly lower than P1. Combination between hydrogel of Terracotem (H1) and time interval of once a five days of watering (P1) was the best treatment combination in improving the growth of sunflower plant in Regosol from Dramaga, Bogor.